Prevalence and predictors of malocclusion among students in special needs schools in Amhara region, Ethiopia - Amare Teshome Tefera; Biruk Girma Bekele; Zelalem Aniley; Aynishet Adane; Tadesse Awoke Ayele; Kefyalew Ayalew Getahun; Simegnew Handebo; Semira Ali; Abebe Muche (BMC Oral Health)
Abstract Background Malocclusion is one of the most common oral health conditions globally, following dental caries and periodontal disease. It affects both function and appearance and can lead to psychological distress, social challenges, and an increased risk of dental diseases. However, little is known about its burden among students with disabilities in Ethiopia. Therefore, this study aimed to assess the prevalence and associated factors of malocclusion among students in special needs schools in the Amhara region, Ethiopia. Methods A school-based cross-sectional study was conducted from November 2020 to April 2021 among students attending special needs schools in the Amhara region, Ethiopia. Data were collected from 396 students attending special needs schools in the region using a pre-designed, structured, interviewer-administered questionnaire. The occlusal status of the study participants was evaluated using Angle’s classification of malocclusion and was leveled as class-I, class-II, or class-III. Multivariable binary logistic regression analysis was done to identify potential predictors of malocclusion among the study participants. Data cleaning and coding were done using EpiData and the analysis was done using SPSS version 26. Results A total of 396 students were involved in the study with a mean age of 16.55 years (± 3.466 SD). The prevalence of malocclusion among students in special needs schools was 42.9% (95%CI; 37.9, 47.9). The magnitude of malocclusion was high among physically disabled (56.0%) and intellectually disabled students (51.7%). The regression analysis indicated that being intellectually disabled (AOR = 3.0, 95% CI: 1.4, 6.3), visually impaired (AOR = 1.9, 95% CI: 1.1, 3.4), and medical comorbidity (AOR = 2.5, 95% CI: 1.2–5.3) were independent predictors of malocclusion among students attending special need schools in Amhara region, Ethiopia. Conclusion and recommendations This study revealed a high prevalence of malocclusion among students in special needs schools. Key predictors included intellectual disability, visual impairment, and the presence of medical comorbidities. These findings underscore the urgent need for accessible orthodontic care for students with disabilities. The Ministry of Health should implement targeted oral health interventions and educational programs, particularly for those with intellectual and visual impairments. Future research should explore the causal pathways linking disability and malocclusion through longitudinal studies to overcome the limitations of cross-sectional data.